Design Configuration of Water Quality Monitoring System in Surabaya: Design Configuration of Water Quality Monitoring System in Surabaya - Moch. Fauzan Rasyid; Moch. Bagus Indrastata; Abdulloh Hamid Nushfi; Anifatul Faricha; Dimas Adiputra; Isa Hafidz; Moch. Iskandar Riansyah; Lora Khaula Amifia (Journal of Computer, Electronic, and Telecommunication (COMPLETE), 2020)
Water have been important needs for human life in many sectors such as in industry, agriculture, and household that its quality must be conserved so is in Surabaya city. The quality of water could influence the quality of human life directly, thus it is important to have an integrated water quality monitoring system. Information regarding water quality monitoring such as pH, dissolved oxygen, turbidity, and conductivity were collected to produce a periodic decision for controlling, analyzing, and fixing the condition of the water. This paper proposed a design configuration of water quality monitoring system for tap water in Surabaya. First, a comparison study of water quality monitoring technology in terms of area, parameter, and methodology from the previous researchers is presented. From the study, the design configuration of water quality monitoring system to be implemented in Surabaya is concluded. The data collection method is better to be done by using Internet of Things (IoT) technology where it is possible to do multiple data type and multiple point real-time data collection throughout the water distribution network remotely.